Effect of strain on the dark current-voltage characteristic of silicon heterojunction solar cells. (15th January 2020) - Guin, L.; Roca i Cabarrocas, P.; Jabbour, M.E.; Triantafyllidis, N.
Highlights: The dark j-V curves of solar cells change reversibly with mechanical deformations. The saturation current shows changes of a few percent for strains of about 10 −3 . The strain-induced changes can be estimated with deformation potential theory. Abstract: Anisotropic mechanical strain as low as 0.1% modifies the electronic response of crystalline semiconductor-based devices and in particular affects the performance of solar cells. We measure the dark current-voltage characteristic of silicon heterojunction solar cells under different levels of tensile uniaxial stress and observe a reversible change of the j - V curve with applied strain. Using a two-exponential description of the j - V characteristic to fit our experimental data, we obtain the strain dependence of the diffusion saturation current and find a decrease of about 3% for a tensile strain level of 6.7 × 10 - 4 . We compare these experiments to a theoretical model that accounts for the effect of strain on the band energy levels, densities of states and mobilities of carriers. The theoretical estimation of the change in saturation current is found to be in reasonable agreement with experimental results.